How was your music festival experience? Impacts on loyalty, word-of-mouth, and sustainability behaviors - Sisson, Annamarie D.; Alcorn, Michelle (Event Management, 2021)
As the popularity of music festivals increases worldwide, an essential component for successful festivals is creating an exceptional guest experience. A conceptual model is proposed, positing that experience economy has a positive effect on loyalty, word-of-mouth (WOM) intentions, and sustainability behaviors of event attendees at a music festival that focuses on sustainability. Multiple regression and structural equation modeling (SEM) were employed to test the model using data collected from 216 attendees at an annual music festival staged in Costa Rica. Results reveal that experience has a positive effect on sustainability behaviors. Additionally, some dimensions of the experience economy have a positive impact on WOM intentions and loyalty. Lastly, WOM intentions have a positive effect on sustainability behaviors. The study provides vital contributions to planning and managing sustainable music festival events. Music festival planners and marketing teams are recommended to offer activities that provide an overall positive experience.
0 citations (Crossref) [2023-10-31]
Keywords: EXPERIENCE ECONOMY; LOYALTY; MUSIC FESTIVALS; SUSTAINABILITY BEHAVIORS; WORD-OF-MOUTH; dept.rec; peer-reviewed